2014
DOI: 10.1007/s00221-014-3827-y
|View full text |Cite
|
Sign up to set email alerts
|

Sleep difficulties are associated with increased symptoms of psychopathology

Abstract: Sleep problems often co-occur with psychopathological conditions and affective dysregulation. Individuals with mood disorders have significantly higher rates of sleep disturbances than healthy individuals, and among those with mood disorders, sleep problems are associated with lower rates of remission and response to treatment. Sleep disruption may itself be a risk factor for various forms of psychopathology, as experimental sleep deprivation has been found to lead to increased affective, cognitive, and somati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 55 publications
5
31
0
Order By: Relevance
“…Tkachenko et al. () furthermore found sleep disturbances associated with higher scores not only for depressive syndromes, but for several dimensions of psychopathology, supporting prior research (Kahn‐Greene, Killgore, Kamimori, Balkin, & Killgore, ). In contrast to the literature, we were not able to replicate the strong correlation between the severity of suicidal ideation and sleep disturbances, which has been reported previously (Winsper & Tang, ).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Tkachenko et al. () furthermore found sleep disturbances associated with higher scores not only for depressive syndromes, but for several dimensions of psychopathology, supporting prior research (Kahn‐Greene, Killgore, Kamimori, Balkin, & Killgore, ). In contrast to the literature, we were not able to replicate the strong correlation between the severity of suicidal ideation and sleep disturbances, which has been reported previously (Winsper & Tang, ).…”
Section: Discussionsupporting
confidence: 56%
“…The present results underline the link between depression and sleep disturbances, as well as between the improvement of sleep disturbances and the degree of psychopathological improvement, which is well accepted in the literature (Thase, 2006). There is also recent evidence suggesting a bidirectional relationship between insomnia and depression (Tkachenko et al, 2014). Several studies have shown that subjective sleep disturbances are a risk factor for the development of both first-onset and recurrent depressive episodes (Baglioni et al, 2011).…”
Section: Sleep Disorders and Outcomementioning
confidence: 99%
“…Due to a high correlation of sleep problems with mood disorders, individuals high on neuroticism experiencing more sleep problems might be more resistant to successful therapy outcomes impacted by an increased worry at bedtime related to getting adequate sleep (Danielsson, Jansson-Fromark, Linton, Jutengren, & Stattin, 2010;Ohayon, 2005;Tkachenko, Olson, Weber, Preer, Gogel, & Killgore, 2014). Perhaps these individuals would benefit from treatment focused on maladaptive beliefs towards sleep and to specifically address concerns and anxiety related to sleep difficulties.…”
Section: Methodsmentioning
confidence: 99%
“…Adult subjects experiencing forced awakenings had significantly less SWS after the first night of sleep deprivation than other participants. Furthermore, in adults who completed the Personality Assessment Inventory, self-reports of recurring sleep problems were associated with symptoms of depression and anxiety 54. The reported frequency of sleep disturbance was closely linked with the severity of the self-reported symptoms.…”
Section: Short-term Health Consequences Of Sleep Disruptionmentioning
confidence: 97%